Pengelompokan Kabupaten/Kota di Pulau Jawa Berdasarkan Kondisi Sosial Ekonomi Sebelum dan Setelah Memasuki Pandemi COVID-19 - Shela Yulfia Hadist; Agung Priyo Utomo (Seminar Nasional Official Statistics, 2021)
Indonesia's economic outlook has turned significantly weaken due to the declaration of the COVID-19 pandemic. Indonesia's economic structure in 2020 spacially dominated by the Java group provinces, contributing 58.75 percent to the national total GDP. COVID-19 pandemic has had the greatest socio-economic impact, particularly on densely populated areas due to the incessant of social restrictions, including the island of Java, the center of the Indonesian economy. This is indicate that if the economy of Java is contracted, the Indonesian economy will also be contracted. This study aims to analyze the socio-economic description of groupings economic in Java before and after into the COVID-19 pandemic based on the variables of economic growth, open unemployment rate, number of workforces, number of leading sectors, per capita expenditure, and percentage of poor people, and compare it before and after entering pandemic using the Cluster Ensemble method. The results obtained indicate that there are economic growth and the number of leading sectors in Java are deteriorating. This study also found that the number of unemployment rate, workforces, poor people, and per capita expenditure, is increasing after facing the COVID-19 pandemic. In the 3 clusters formed in 2019 and 5 clusters formed in 2020, it is generally found that the grouping of each cluster was not significantly different, but there were some differences in the characteristics and members of the cluster.